The Effectiveness of Quality of Life Therapy on Depression and Anxiety among Patients with Multiple Sclerosis - Hashemi, Leila; Rahimi, Changiz; Mohammadi, Nurollah (International Journal of Applied Behavioral Sciences, 2018)
Introduction: Many patients with incurable disease, like multiple sclerosis (MS), experience depression and anxiety, therefore, this study aimed at investigating the effectiveness of quality of life therapy (QOLT) among patients with multiple sclerosis (MS), depression and anxiety. Methods: The design of the study was semi-experimental with an experimental group and a control group, including three phases; a pre-test, a post-test and a follow-up test. Statistical population consisted of patients suffering from MS referring to health centers in Shiraz, Iran. 24 patients were selected using convenience-sampling method. They were randomly assigned to the experimental and control groups (each 12 members). The experimental group received QOLT during eight 50minute weekly sessions. The control group received no treatment. All participants completed the Beck Depression Inventory–II and Beck Anxiety Inventory. The data were analyzed using the analysis of covariance method. Results: Comparison of the means of depression and anxiety scores of two groups in post-test phase showed that quality of life therapies had significant effects on reduction of depression (p<0.001) and anxiety (p<0.001) rates in MS patients. Comparing two groups in a follow-up phase showed that the effect of intervention was stable. Conclusion: This research showed that quality of life therapy has decreased depression and anxiety rate significantly in MS patients. It seems that using psychological intervention can improve the well-being of MS patients and they can benefit from the positive effects of a quality time program. Therefore, it is recommended that, in addition to prescription of medications, psychological interventions be done for these patients. Declaration of Interest: None